“Creating What I Think I should Be Doing”: Contradictions and Learning of College Job Changers - Joann S. Olson; Junghwan Kim (Adult Education Research Conference, 2017)
This roundtable, and the study it is based on, outlines how non-faculty staff at a small college described their own workplace learning after a “significant” job change (as defined by the participant).
Keywords: higher education; workplace learning; career development; cultural-historical activity theory